Music videomemetics. Digital conversations, direct dialogues, paramemetics, counter-publics and digital impoliteness - López Cano, Rubén (Revista Musical Chilena, 2023)
The exchange of internet memes on the web encourages digital conversations. Based on interviews, virtual ethno- graphy and audiovisual analysis, this article exposes the different levels of digital conversations produced from a specific type of music video memes; makes explicit the mechanisms of direct digital dialogues (when a remix responds, criticizes, amplifies or improves to another previous specific videomeme) and describes the dynamics of paramemetic conversations (interactions in the comments section on platforms such as YouTube or Facebook) highlighting the emergence of counterpublics and digital impoliteness. The peculiar processes of memetic development and transformation in music video memes are also pointed out.